O MODELO PREDOMINANTE DE MASCULINIDADE EM QUESTÃO - Simone Cabral Marinho dos Santos (Universidade Federal do Maranhão, 2010)
This article will discusses the process of disintegration of masculine control over the feminine one, what not only comes from the redefinition of women ́s role in society today, but also from the historical transformations that have occurred and thus questioned the myth of masculinity. A new definition of what actually is to become a man has been presented, based on conflicts in the spheres of subjectivity and intimacy. We’ll try, therefore, to put together, in this article, elements that can contribute towards a reflection about the masculine ideal that is based upon the supposedly unfailing masculine dominator archetype in patriarchal society.